PENERAPAN TABUNG BAHAN BAKU DESTILASI MINYAK NILAM BERBAHAN STAINLESS STEEL PADA PENGHASIL MINYAK NILAM - Rina Rina; Yuli Yetri; Roni Kurniawan Putra; Adriansyah Adriansyah; Teguh Yaman Telaumbanua; Annisa Khairiyah; Syukri Syukri (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The problem faced by partners today is the low technology used in the patchouli oil refining process. The distillation system equipment used is still simple, the tubes are made of used drums and are easy to rust. This service aims to make a patchouli oil distillation device whose tube is made of stainless steel and to test the tool. The implementation begins with a field survey by conducting discussions related to partner problems and the solutions provided. The manufacturing process is carried out in three stages of activity, namely tool design, tool manufacture, and tool testing. The manufacture is carried out in a workshop located in Sungai Sapih, Kuranji Padang. While the test was carried out in a patchouli plantation located in Lubuk Minturun, Padang. The results show that using a tube made of stainless steel produces patchouli oil cleaner than used drum. Therefore the Mitra does not screen after the distillation process. The process of production becomes effective and efficient.